Landslide Monitoring Network Establishment within Unified Datum and Stability Analysis in the Three Gorges Reservoir Area. (20th September 2017) - Huang, Shengxiang; Li, Chenfeng; Luo, Li
Abstract : A landslide monitoring network construction within unified datum which combined fiducial points, working reference points, and monitoring points was intensively studied in the Three Gorges Reservoir area. With special long and narrow geographical location in the area, designing and building monitoring network was vital to the realization of landslide monitoring. To build such a network with high precision, this paper mainly focused on the following four aspects: (1 ) method of using multiple GPS reference stations to build a unified datum network and subnet adjustment, (2 ) GPS data processing algorithm with millimeter level, (3 ) analysis of influence on the adjustment resulting from systematic error of time evolution datum from different GPS observations, and (4 ) establishment and stability analysis of unified datum. Then, using global test and trial-and-error method to analyze the datum based on the GPS observations (2008~2011) of landslide monitoring network in the area, we concluded that there were moved reference points during the three years of high water impoundment, and the horizontal displacement of moved reference points was more than 4 cm, even up to 79.4 cm. The displacement direction of unstable reference points was inspected with geographical environment at sites, which revealed congruency between them.